1984
DOI: 10.5962/bhl.title.43347
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preconditioning temperatures and neuropeptides on metabolic and endocrine responses of rats in the heat / by Andrea Rose Gwosdow.

Abstract: for his patience, support and valuable advice in the planning and execution of this significant, original and independent research project. The guidance, cooperation and assistance of members of her committee, Drs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 95 publications
(196 reference statements)
0
4
0
Order By: Relevance
“…Altered pituitary responsiveness to hypothalamic releasing factors has also been reported in PVN-lesioned rats (35). Although rat and mouse pituitary contains IL-1 receptors and IL-1 has a stimulatory effect on AtT20 cells (40), normal pituitary tissue seem to be insensitive to IL-I, in terms of ACTH release. Disruption of hypothalamic inputs (by PVN-lesion or other manipulations) could result in changes in IL-1 receptor density and/or affinity and post-receptor events in the pituitary.…”
Section: Discussionmentioning
confidence: 92%
“…Altered pituitary responsiveness to hypothalamic releasing factors has also been reported in PVN-lesioned rats (35). Although rat and mouse pituitary contains IL-1 receptors and IL-1 has a stimulatory effect on AtT20 cells (40), normal pituitary tissue seem to be insensitive to IL-I, in terms of ACTH release. Disruption of hypothalamic inputs (by PVN-lesion or other manipulations) could result in changes in IL-1 receptor density and/or affinity and post-receptor events in the pituitary.…”
Section: Discussionmentioning
confidence: 92%
“…But comfort is also influenced by tactile perceptions resulting from contact interactions between the moisture, the fabric surface, and the skin. Studies [ 8,12 ] have demonstrated that an altered contact behavior of fabric against the skin is responsible for uncomfortable feelings when moisture builds up on the fabric surface, in the microclimate, and on the skin. Gwosdow et al [ 8 ] studied the relationship between changes in room conditions and skin-fabric friction.…”
mentioning
confidence: 99%
“…Studies [ 8,12 ] have demonstrated that an altered contact behavior of fabric against the skin is responsible for uncomfortable feelings when moisture builds up on the fabric surface, in the microclimate, and on the skin. Gwosdow et al [ 8 ] studied the relationship between changes in room conditions and skin-fabric friction. They demonstrated that the frictional force required .for fabric to move against sweating skin (resulting from a high room temperature and humidity) was much higher than for movement against dry skin, i.e., as skin wetness increased, frictional force also increased.…”
mentioning
confidence: 99%
See 1 more Smart Citation